2011
DOI: 10.1186/cc10448
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacodynamic model of bicarbonate response to acetazolamide in mechanically ventilated chronic obstructive pulmonary disease patients

Abstract: IntroductionAcetazolamide is commonly given to chronic obstructive pulmonary disease (COPD) patients with metabolic alkalosis. Little is known of the pharmacodynamics of acetazolamide in the critically ill. We undertook the pharmacodynamic modeling of bicarbonate response to acetazolamide in COPD patients under mechanical ventilation.MethodsThis observational, retrospective study included 68 invasively ventilated COPD patients who received one or multiple doses of 250 or 500 mg of acetazolamide during the wean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…This study is a continuation of our previous published work [15]. The results of the present study suggest that higher doses of acetazolamide are necessary to induce a substantial increase in minute ventilation and hence a decrease in PaCO 2 in alkalotic mechanically ventilated COPD patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study is a continuation of our previous published work [15]. The results of the present study suggest that higher doses of acetazolamide are necessary to induce a substantial increase in minute ventilation and hence a decrease in PaCO 2 in alkalotic mechanically ventilated COPD patients.…”
Section: Discussionsupporting
confidence: 82%
“…This cohort has been previously described [15]. Due to the observational design, patient consent was waived, in accordance with French bioethics laws.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been reported that non-responders to acetazolamide (defined by a reduction of PaCO 2 of less than 5 mm Hg) have a more severe airflow limitation than responders [48]. This finding has not been confirmed in later studies [16]. …”
Section: Clinical Datamentioning
confidence: 95%
“…Mixed acid-base balance disturbances (the association of chronic respiratory acidosis and metabolic alkalosis) can also be observed. Indeed, in mechanically ventilated patients with COPD, the most frequently observed acid-base disorders are mixed [15,16]. In this context, respiratory acidosis is the consequence of hypercapnia.…”
Section: Metabolic Alkalosis In the Intensive Care Unitmentioning
confidence: 99%
“…Moreover, several factors, such as co-administration of furosemide or systemic steroid, can interfere with ACET pharmacokinetics (5). In the study performed by Rialp Cervera et al (1), co-treatments with diuretics (69% vs. 71%), steroids (4% vs. 13%), catecholamines (35% vs. 50%), were not used in the same proportion in the two groups (although the difference has no statistical significance), theses therapeutics can interfere with ACET pharmacokinetics and affect ACET's effectiveness (5).…”
mentioning
confidence: 99%